Exploring the Pedagogical Applications of Cultural Resources in Secondary Level Classroom Practices - Bhattarai, Tara Nath (SNPRC Journal, 2025)
This paper examines the pedagogical uses of cultural resources in the context of secondary-level classroom settings in developing contextualized and skill-oriented learning environments. The application of a qualitative research approach with a phenomenological focus was used to examine the lived experiences of teachers and learners in the use of local knowledge in instructional settings. Data was gathered using classroom observation and semi-structured interviews. The results show that contextualization of culturally embedded resources in classroom instruction increases student engagement, understanding, and skill development, closing the gap between academic knowledge and everyday life. The research concludes that making secondary education relevant to the socio-cultural reality of learners can result in more significant and sustainable learning outcomes. It also recommends strategies for the use of socio-cultural resources in secondary education through contextualized and test-based learning frameworks.